2013
DOI: 10.1002/bmc.2868
|View full text |Cite
|
Sign up to set email alerts
|

LC‐MS/MS determination and pharmacokinetic study of lacidipine in human plasma

Abstract: A robust, specific and fully validated LC-MS/MS method as per general practices of industry has been developed for estimation of lacidipine (LAC) with 100 μL of human plasma using lacidipine-(13) C8 as an internal standard (IS). The API-4000 LC-MS/MS was operated under the multiple reaction-monitoring mode. A simple liquid-liquid extraction process was used to extract LAC and IS from human plasma. The total run time was 3.0 min and the elution of LAC and IS occurred at 1.96 and 1.97 min; this was achieved with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…10,11 Table S5 † shows information from some studies involving CCBs in biological samples, such as analysis techniques, extraction techniques, type of sample, LOQ and LOD. [35][36][37][38][39][40][41] It is important to note that few studies employed SPE techniques, as for example PT-SPE reported in this work, with low sample and solvent consumption (mL instead of mL) and a small amount of material (20 mg). Despite some methods that use mass spectrometry detection having LOQ < 3 ng mL −1 , when compared to others that use UV detection, the LOQ reported in this work is the lowest ever found, demonstrating the innovation and applicability of this work that achieved recoveries around 100%.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…10,11 Table S5 † shows information from some studies involving CCBs in biological samples, such as analysis techniques, extraction techniques, type of sample, LOQ and LOD. [35][36][37][38][39][40][41] It is important to note that few studies employed SPE techniques, as for example PT-SPE reported in this work, with low sample and solvent consumption (mL instead of mL) and a small amount of material (20 mg). Despite some methods that use mass spectrometry detection having LOQ < 3 ng mL −1 , when compared to others that use UV detection, the LOQ reported in this work is the lowest ever found, demonstrating the innovation and applicability of this work that achieved recoveries around 100%.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…High therapeutic index of dihydropyridines has promoted the analytical method development for their assessment in bulk, dosage and in biological fluids. Literature study reveals that several analytical methods for the quantitative determination of dihydropyridines such as spectrophotometry [26,27], spectrofluorimetry [28], electrochemical methods [29] and HPLC-MS [30,31] have been reported. The inherent simplicity, reproducibility and highly selective nature of analysis make the liquid chromatography based estimations as the most suitable for quality control laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…The active trans form is used in therapy (32)(33)(34)(35)(36) . Some analytical methods for the determination of lacidipine alone or/and combination with other drug in pharmaceutical dosage form and biological fluids have been reported, including some spectrophotometric method (37,38) , HPLC (39)(40)(41)(42)(43) , Stability-Indicating LC Method (44,45) high performance thin layer chromatography (HPTLC) (46) , LC-MS/MS methods (47)(48)(49)(50) , ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method (51) and SFC-MS/MS (52) . Monotherapy with various antihypertensive agents is not always sufficient to control the blood pressure and concomitant use of two or more drugs is necessary in 50% of the hypertensive patients (19) .…”
Section: Introductionmentioning
confidence: 99%